giải các phương trình sau a) x^2 ( 6 – x ) – 49 ( 6 – x ) = 0 b) ( x – 2 )^2 = 64x^2 + 16x + 1 c) x + 3 / x – 2 + x + 1 /

giải các phương trình sau
a) x^2 ( 6 – x ) – 49 ( 6 – x ) = 0
b) ( x – 2 )^2 = 64x^2 + 16x + 1
c) x + 3 / x – 2 + x + 1 / x + 2 = 2x^2 – 4 / x^2 – 4

2 bình luận về “giải các phương trình sau a) x^2 ( 6 – x ) – 49 ( 6 – x ) = 0 b) ( x – 2 )^2 = 64x^2 + 16x + 1 c) x + 3 / x – 2 + x + 1 /”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
     a) x^2 (6-x) – 49(6-x)=0
    <=> (x^2-49)(6-x)=0
    \(\left[ \begin{array}{l}x^2-49=0\\6-x=0\end{array} \right.\) \(\left[ \begin{array}{l}x^2=49\\x=6\end{array} \right.\)  \(\left[ \begin{array}{l}x=7\\x=6\end{array} \right.\) 
    Vậy S={7;6}
    c) (x+3)/(x-2) + (x+1)/(x+2)=(2x^2-4)/(x^2-4)
    MTC : (x-2)(x+2)
    ⇔[(x+2)(x+3)]/[(x-2)(x+2)] + [(x+1)(x-2)]/[(x-2)(x+2)] = (2x^2-4)/[(x-2)(x+2)]
    ⇔(x+2)(x+3) + (x+1)(x-2)=2x^2-4
    ⇔x^2 +3x + 2x+6 + x^2-2x + x-2=2x^2 -4
    ⇔(x^2+x^2-2x^2) + (3x+2x-2x) = -4-6+2
    ⇔3x = -8
    ⇔x=-8/3
    Vậy S={-8/3}
    b)(x-2)^2=64x^2+16x+1
    ⇔-63x^2-20x+3=0

    ⇔-63x^2+7x-27x+3=0

    ⇔-7x(9x -1) -3(9x-1)=0

    ⇔-7x(9x -1) -3(9x-1)=0
    ⇔(-7x-3)(9x-1)=0\(\left[ \begin{array}{l}-7x-3=0\\9x-1=0\end{array} \right.\) \(\left[ \begin{array}{l}x=-3/7\\x=1/9\end{array} \right.\) 
    Vậy S={-3/7;1/9}

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
      a) x² ( 6 – x ) – 49 ( 6 – x ) = 0
    ⇔ ( x² – 49 ) ( 6 – x ) = 0
    ⇔ ( x + 7 ) ( x – 7 ) ( 6 – x ) = 0
    TH1 : x + 7 = 0
    ⇔ x = -7
    TH2 : x – 7 = 0
    ⇔ x = 7
    TH3 : 6 – x = 0
    ⇔ x = 6
    ⇒ S = { ±7 ; 6 }
    b) ( x – 2 )² = 64x² + 16x + 1
    ⇔ ( x – 2 )² = ( 8x + 1 )²
    ⇔ ( x – 2 )² – ( 8x + 1 )² = 0
    ⇔ ( x – 2 + 8x + 1 ) ( x – 2 – 8x – 1 ) = 0
    ⇔ ( 9x – 1 ) ( -7x – 3 ) = 0
    TH1 : 9x – 1 = 0
    ⇔ 9x = 1
    ⇔ x = 1/9
    TH2 : -7x – 3 = 0
      ⇔ -7x = 3
    ⇔ x = -3/7
    ⇒ S = { 1/9 ; -3/7 }
    c) $\dfrac{x+3}{x-2}$ + $\dfrac{x+1}{x+2}$ = $\dfrac{2x²-4}{x²-4}$ ( Đkxđ x $\ne$ ±2 )
    ⇔ $\dfrac{x+3}{x-2}$ + $\dfrac{x+1}{x+2}$ – $\dfrac{2x²-4}{(x+2)(x-2)}$ = 0
    ⇔ $\dfrac{(x+3)(x+2)+(x+1)(x-2)-2x²+4}{(x+2)(x-2)}$ = 0
    ⇒ x² + 2x + 3x + 6 + x² – 2x + x – 2 – 2x² + 4 = 0
    ⇔  4x + 8 = 0
      ⇔ 4x = -8
    ⇔ x = -2 ( KTM )
    ⇒ S = $\emptyset$

    Trả lời

Viết một bình luận

Câu hỏi mới